SARS-CoV-2 Genome Structure, Pathogenesis, Issues, and Challenges in Laboratory Diagnosis - Nath, Gopal; Pandey, Sanjay K.; Kumar, Nishant; Gupta, Munesh Kumar (Annals of the National Academy of Medical Sciences (India), 2023)
Severe acute respiratory syndrome coronavirus 2 causing coronavirus disease 2019 pandemic disease is an enveloped virus, showing genome similarity with bat coronavirus. This virus initially infects the upper respiratory tract, with subsequent spread to the lower respiratory tract. Despite the availability of antigen and antibody detection methods, reverse transcription-polymerase chain reaction (RT-PCR) is the diagnostic test of choice for this novel coronaviral infection. Care must be taken while interpreting the RT-PCR results, as single RT-PCR, especially in early days of infection, maybe false negative. The availability of cartridge-based nucleic acid amplification test has improved the diagnostic facilities in a peripheral setting of developing countries.
Keywords: SARS-CoV-2; COVID-19; RT-PCR; TrueNAT; antigen